2019
DOI: 10.5212/terraplural.v.13i3.0009
|View full text |Cite
|
Sign up to set email alerts
|

Habitação de Interesse Social como política pública e implementação do Programa ‘Minha Casa, Minha Vida’ em cidades médias, o caso de Erechim, RS, Brasil

Abstract: This paper presents a brief contextualization of the recurrent Public Policies in Brazil, adopted as a guarantee of access to housing, as a right guaranteed by the Federal Constitution of 1988. The analysis is also made of how these Public Policies were reflected in the Municipality of Erechim, and it is evaluated how the City Hall, responsible for planning the land uses and manager of Public Policies, according to the City Statute of 2001, has acted in the regulation of these policies. The study was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…"According to [6], the distinction between the production of social housing (promoted by the State) and that one aimed at market housing has blurred, forming a hybrid intermediate zone-social market housing" [6] (p. 120). As pointed by [83]: An important observation is that Band I, which has more demand, is generally not met, since the partnership between residents, city hall and construction companies is not always consolidated, mainly due to the "disinterest of the construction companies that reported that the profit is lower than that of those served in Band II" [6] (p. 117).…”
Section: Discussion About the Inefficiency Of The Zeis To Fight Social Segregationmentioning
confidence: 99%
See 1 more Smart Citation
“…"According to [6], the distinction between the production of social housing (promoted by the State) and that one aimed at market housing has blurred, forming a hybrid intermediate zone-social market housing" [6] (p. 120). As pointed by [83]: An important observation is that Band I, which has more demand, is generally not met, since the partnership between residents, city hall and construction companies is not always consolidated, mainly due to the "disinterest of the construction companies that reported that the profit is lower than that of those served in Band II" [6] (p. 117).…”
Section: Discussion About the Inefficiency Of The Zeis To Fight Social Segregationmentioning
confidence: 99%
“…It ends up creating more segregated areas in the city, often without the minimum conditions of urbanity. In many cases the areas were not served by public transport, without any kind of service nearby, such as UBS (basic health unit), day care centers, schools, among others, such as post offices, which often do not provide services in these areas" [83] (p. 117), a position that is shared with other authors [77,[84][85][86].…”
Section: Discussion About the Inefficiency Of The Zeis To Fight Social Segregationmentioning
confidence: 99%